The Effect of Profitability, Leverage, dnd Company Size on Audit Delay - Satriadi, Dodi (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2022)
The research was conducted on Property and Real Estate Companies listed on the Indonesia Stock Exchange in 2017 – 2020 using descriptive and verification research methods using a quantitative approach. The sampling technique used was purposive sampling in order to obtain 35 companies that met the criteria. The purpose of this study was to determine the effect of profitability, leverage, and company size on audit delay. Technical analysis of this research using multiple linear regression analysis. The results in this study indicate that the variable profitability, leverage, and firm size have an effect on audit delay either simultaneously or partially